Sublytic complement C5b-9 complexes induce thrombospondin-1 production in rat glomerular mesangial cells via PI3-k/Akt: association with activation of latent transforming growth factor-β1 - Gao, L (Blackwell Science Inc, 2006)
Mesangial cell proliferation is a common cellular response to a variety of different types of glomerular injury. Complement C5b-9 is a prime candidate to mediate mesangial cell proliferation, especially sublytic C5b-9, which can induce the production of multiple inflammatory factors and cytokines. Transforming growth factor (TGF)-β1 plays a major role in the accumulation of extracellular matrix (ECM), while thrombospondin (TSP)-1 has been identified as an activator of latent TGF-β1 in an in vitro system. Using rat glomerular mesangial cells (GMCs) as a model system, we assessed the effect of sublytic C5b-9 on the expression of TSP-1 and TGF-β1 and explored the relevant pathway of signal transduction. First, we ensured the concentrations of anti-Thy1 antibody and complement, which were regarded as a sublytic C5b-9 dose, and examined whether the sublytic C5b-9 induced expression of TSP-1 in rat GMCs which, in turn, activated latent TGF-β1 by real-time polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA), respectively. Then, we investigated the role of the PI3-k/Akt pathway in sublytic C5b-9-induced TSP-1 production in rat GMCs by Western blot analysis. The addition of sublytic C5b-9 (5% anti-Thy1 antibody and 4% normal serum) to rat GMCs induced activation of latent TGF-β1 via TSP-1. The addition of sublytic C5b-9 apparently increased the protein of Akt phosphorylation, whereas PI3-k inhibitor LY294002 could clearly reduce the increase of TSP-1 induced by sublytic C5b-9. These results indicate that TSP-1 is an activator of latent TGF-β1 in sublytic C5b-9-induced rat GMCs; furthermore, the PI3-k/Akt signal transduction pathway may play a key role in sublytic C5b-9-induced TSP-1 production.